Identifying the causes of food insecurity and household coping behaviors in Southern Niger - Zakari, Seydou (Dynamics of Rural Society Journal, 2026)
Despite significant efforts by the Nigerien government and several international organizations, such as the World Food Program (WFP) and various non-governmental organizations (NGOs), food insecurity continues to affect a substantial portion of the Nigerien population. This study aims to identify the causes of food insecurity and examine the coping strategies adopted by households to mitigate hunger. A structured survey was conducted in 15 villages in the Kollo region of Niger, where household heads were randomly selected for interviews. A total of 500 households participated. Using the Multinomial Probit model, the study explores factors influencing households' choices of coping strategies, hypothesizing that these behaviors are shaped by socio-economic and demographic characteristics. The results reveal that food insecurity is driven by factors such as drought, soil infertility, lack of agricultural inputs, crop pests and diseases, and limited financial resources. In response, households employ strategies such as selling livestock, migrating in search of better opportunities, consuming less preferred foods, and resorting to unusual borrowing. The study concludes that enhancing the sustainability of agricultural production through the promotion of climate-smart agricultural technologies is crucial for improving food security and strengthening household resilience to future challenges.